‘See Me, Feel Me’: Prismatic Adaptation of an Alien Limb Ameliorates Spatial Neglect in a Patient Affected by Pathological Embodiment - Ronga, Irene; Garbarini, Francesca; Neppi-Modona, Marco; Fossataro, Carlotta; Pyasik, Maria; Bruno, Valentina; Sarasso, Pietro; Barra, Giulia; Frigerio, Marta; Chiotti, Virginia Carola; Pia, Lorenzo (Frontiers in Psychology, 2019)
Pathological embodiment (E+) is a specific contralesional delusion of body ownership, observed following brain damage, in which patients embody someone else’s arm and its movements within their own body schema whenever the ‘alien’ arm is presented contralesionally in a body-congruent position (i.e., 1st person perspective and aligned with the patient’s shoulder). This disorder is often associated with spatial neglect, a neurological syndrome in which patients are unaware of stimuli presented in the contralesional (left) space. Capitalizing on previous evidence demonstrating that prismatic adaptation of the ipsilesional arm to right-deviating prisms is effective in ameliorating neglect symptoms, here we investigated whether such amelioration also occurs in E+ patients with neglect when prismatic training is performed by the ‘alien’ embodied arm. Four neglect patients (one with and three without pathological embodiment) underwent visuomotor prismatic training performed by an ‘alien’ arm. Specifically, while patients were wearing prismatic goggles shifting the visual field rightward, a co-experimenter’s left arm presented in a body-congruent perspective was repeatedly moved toward visual targets by another examiner. In a control condition, the co-experimenter’s arm was moved towards the targets from a body-incongruent position (i.e., 3rd person perspective). Neglect symptoms were assessed before and after training through paper-and-pencil tasks. Following 1st person perspective training, neglect in the E+ patient improved significantly more than following 3rd person perspective training, suggesting that prismatic adaptation of the ‘alien’ embodied arm is effective in modulating spatial representation. Conversely, for control E- patients, not embodying the ‘alien’ arm, we observed more limited improvements following training. These findings indicate that the ’alien’ arm is so deeply embedded in the neglect patient body and motor schema that adaptation to prismatic lenses can affect multiple processing stages, from low level sensory-motor correspondences, to higher level body, motor and spatial maps, similarly as it occurs in normal subjects and neglect patients without pathological embodiment.